The Factors Affecting STIE Yapis Dompu Students’ Interest in Entrepreneurship - Ega Saiful Subhan; Budi Eko Soetjipto; Cipto Wardoyo (Syntax Corporation Indonesia, 2022)
This research aims to acknowledge the effect of non-formal education, social and family environment, information technology, and business capital on entrepreneurial interest in STIE Yapis Dompu students. This research is a quantitative descriptive and analytic study with a survey method at STIE Yapis Dompu titled